Accuracy of ultrasound performed by medical residents in operating rooms in identifying parathyroid glands in patients with hyperparathyroidism - Regison Rafael Dias Silva; Giovanni Simões de Medeiros; Murilo Catafesta das Neves (Brazilian Journal of Otorhinolaryngology, 2025)
Objective: To describe the findings of US examinations performed by Head and Neck Surgery (HNS) resident physicians in patients in the preoperative period immediately before parathyroidectomy, and to compare these results with those of examinations performed preoperatively (ultrasonography and/ or scintigraphy) and with the findings of surgical procedures. Methods: Patients in the preoperative period of parathyroidectomy underwent US examinations performed by HNS resident physicians after induction of anesthesia. The findings were registered and later compared with those of preoperative and intraoperative examinations using descriptive statistical analysis and calculation of sensitivity, specificity, and accuracy. Results: At least one gland was identified in 81% of the patients, most commonly the left inferior parathyroid. There was 63% agreement between the examinations performed in the operating room and the preoperative examinations. Sensitivity of 76%, specificity of 100%, and accuracy of 81.25% were evidenced in identifying parathyroids > 5 mm in patients with hyperparathyroidism associated with Chronic Kidney Disease (CKD), and sensitivity of 33% was found in patients with primary hyperparathyroidism. Conclusion: US examinations performed by HNS resident physicians in patients preoperatively to parathyroidectomy are accurate (81.25%) in identifying parathyroids compared with intraoperative findings in patients with hyperparathyroidism associated with CKD. Level of evidence: Level III.